Worldwide research on open innovation in SMEs - David Sabando-Vera; Marcela Yonfa-Medranda; Néstor Montalván-Burbano; Jose Albors-Garrigos; Katherine Parrales-Guerrero (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Research on open innovation (OI) has increased in recent years, showing its potential in various areas of knowledge. Its relation to small and medium-sized enterprises has attracted the attention of academics. This article aims to evaluate the intellectual structure of the scientific study of OI, and its close relationship with various scientific fields, through a bibliometric analysis of this academic field using the Scopus database and the application of the VOSviewer software. The methodology comprises a rigorous systematic and transparent process divided into four phases: (i) the establishment of search criteria for the research field, through a literature review for its selection; (ii) the selection of the database, the establishment of the search equation and extraction of information; (iii) the application of inclusion and exclusion criteria for the selected documents and an explanation of the usefulness of the software; and (iv) the analysis of the results through the approaches of scientific output performance and bibliometric mapping. The results show an increasing trend of IO publications in SMEs, consolidated in 396 articles with contributions from 65 countries and 947 authors. The intellectual structure shows seven themes related to firm performance, R&D networks, business management, business models, capabilities and knowledge transfer. This study contributes to the field by providing an overview of IO in SME contexts. It also provides insightful information to policymakers for developing policies for firm economic growth.
Keywords: 650; bibliometric analysis; co-citation analysis; open innovation; small and medium enterprise; SMEs